2009
DOI: 10.1590/s0100-83582009000500020
|View full text |Cite
|
Sign up to set email alerts
|

Resistência de genótipos de soja ao herbicida glyphosate

Abstract: RESUMO -Avaliou-se a resistência de dez genótipos de soja (Glycine max) ao herbicida glyphosate. Foi adotado o esquema fatorial 10 x 4, no delineamento em blocos casualizados, com quatro repetições. O fator A foi composto por dez genótipos de soja, e o B, por quatro doses de glyphosate. A aplicação do herbicida foi realizada no momento em que as plantas de soja apresentavam a segunda folha trifoliolada completamente desenvolvida. Avaliaramse os caracteres: intoxicação das plantas, número de nós da haste princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Other characteristics, such as dry weight of stems ( Figure 3D), number of branches in the main stem ( Figure 3E), and dry weight of pods ( Figure 3F) decreased at the application rates of 0.06% and 0.12% of the herbicide. In the case of plants tolerant to glyphosate, in general, there were no negative effects, as also reported by Kruse et al (2000), Matsuo et al (2009), and Correia and Durigan (2007). All these vegetative characteristics together showed that recovery of tolerant plants is satisfactory, but in the case of sensitive cultivars, there are persistent losses in the plant cycle due to the herbicide rate used in the germination bioassay (Albrecht et al 2014).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…Other characteristics, such as dry weight of stems ( Figure 3D), number of branches in the main stem ( Figure 3E), and dry weight of pods ( Figure 3F) decreased at the application rates of 0.06% and 0.12% of the herbicide. In the case of plants tolerant to glyphosate, in general, there were no negative effects, as also reported by Kruse et al (2000), Matsuo et al (2009), and Correia and Durigan (2007). All these vegetative characteristics together showed that recovery of tolerant plants is satisfactory, but in the case of sensitive cultivars, there are persistent losses in the plant cycle due to the herbicide rate used in the germination bioassay (Albrecht et al 2014).…”
Section: Resultssupporting
confidence: 71%
“…An assay performed by Gris et al (2013) showed that herbicide application on herbicide-tolerant plants under either field or greenhouse conditions, which would be more stressful conditions than germination in a moistened substrate with glyphosate, did not change seed physiological quality, confirming the result of plant recovery in this study. Matsuo et al (2009) did not observe symptoms from herbicide in tolerant plants after they were sprayed with glyphosate under Figure 1. Reduction in the hypocotyl (A), radicle (B), and seedling (C) length due to concentration of herbicide acid equivalent of 0, 0.03, 0.06, and 0.12 %.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…For soybean, analyses of genetic diversity have been widely applied. The presence of genetic variability among genotypes was observed by Miranda et al (2001), Miranda et al (2007), Matsuo et al (2009), Vieira et al (2009 and Almeida et al (2011). Also focusing on the soybean cyst nematode, Ma et al (2006) studied the genetic diversity of soybean and created a core collection based on this resistance.…”
Section: Introductionmentioning
confidence: 99%